Labor Protection and Leverage - Simintzi, Elena; Vig, Vikrant; Volpin, Paolo (Review of Financial Studies, 2015)
This paper exploits intertemporal variations in employment protection across countries and finds that rigidities in labor markets are an important determinant of firms' capital structure decisions. Over the 1985–2007 period, we find that reforms increasing employment protection are associated with a 187 basis point reduction in leverage. We interpret this finding to suggest that employment protection increases operating leverage, crowding out financial leverage. This result does not appear to be due to pretreatment differences between treated and control firms, omitted variables, unobserved changes in regional economic conditions, and reverse causality. Heterogeneous treatment effects are consistent with our economic intuition.